The Speed of Adjustment and the Sequencing of Economic Reforms : Issues and Guidelines for Policymakers - Nsouli, Saleh (IMF Working Papers; Working Paper ;, 2002)
This paper reviews the issues involved in determining the appropriate speed of adjustment and the sequencing of economic reforms, focusing on considerations relevant to policymakers. It points out that the debate between the protagonists of a high-speed approach and those favoring a gradualist approach is based primarily on the weights given to adjustment costs, policy credibility, reform feasibility, and risk assessment. It underscores the importance of appropriate sequencing and the impact of sequencing on the speed of adjustment and reforms. The paper concludes by highlighting factors that policymakers should consider when selecting their approach toward speed and sequencing.